The Influence of Pregnancy Massage on the Level of Anxiety Facing Childbirth in Third Trimester Pregnant Women in Jakarta, Banten, West Java, South Sumatra - Rahayu Khairiah; Dinis Rizki Alfiyani; Eha Julaeha; Noviana Maulani; Rina Astina; Sadariah; Tria Suselowaty (Postgraduate, University of Mataram, 2026)
Anxiety among pregnant women approaching labor can lead to prolonged delivery, complications, and increased risk of maternal and fetal mortality. According to the World Health Organization (WHO), anxiety disorders contributed to approximately 15% of global morbidity rates in 2022. One of the non-pharmacological interventions to reduce anxiety is pregnancy massage. This study aimed to determine the effect of pregnancy massage on the level of anxiety among third-trimester pregnant women facing childbirth in Indonesia. This research employed a pre-experimental design with a one-group pretest–posttest approach. The study involved 180 third-trimester pregnant women selected using a purposive sampling technique. Data were analyzed using the Wilcoxon test after confirming data normality. Before receiving pregnancy massage, most respondents (78.3%) experienced moderate anxiety with an average score of 24.67. After the intervention, 91.7% of respondents showed mild anxiety with a decreased average score of 18.65. Statistical analysis using the Wilcoxon test revealed a significant difference between pretest and posttest anxiety levels (p = 0.000), indicating that pregnancy massage effectively reduces anxiety in pregnant women facing labor. These findings support the use of non-pharmacological interventions to promote maternal mental well-being during the perinatal period. Pregnancy massage has a significant effect in reducing anxiety levels among third-trimester pregnant women facing childbirth.